Building recovery ready communities: the recovery ready ecosystem model and community framework. (2nd January 2020) - Ashford, Robert D.; Brown, Austin M.; Ryding, Rachel; Curtis, Brenda
Abstract: Background: Public and private systems in the United States and around the World are impacted by substance use disorders (SUD). Despite recent attempts at bringing top down solutions, SUDs continue to be a leading cause of death, a leading correlate in violent crime, and a leading cause of lost productivity in the workplace. Community-based resources have been shown to positively affect SUD impact and SUD recovery, by orienting stakeholders towards the problem and creating continuity among support services. Community-based innovations, such as recovery community organizations and other recovery support services, have provided evidence of successfully scaling recovery efforts and improving the chance of sustained recovery for individuals that live within the community. Methods: A theoretical model and framework, grounded in the recovery-oriented systems of care (ROSC) theorems, is proposed to identify components and connections that support a community's ability to support individual and group recovery from SUD. Results: The Recovery Ready Ecosystem Model (RREM) and Recovery Ready Community Framework builds upon the early work of the ROSC, highlighting recently emboldened support structures such as harm reduction, educational recovery programs, and other traditional support structures in communities. Conclusions: Enhanced community needs assessment can be informed by the RREM and Recovery Ready Community framework to identify gaps in their current community infrastructure. Further testing of the recovery readiness equation should be performed as a potential measure of efficacy of community ability to support long-term recovery from SUD. Exploration of potential application of the model and framework to international settings is also needed.